Perbedaan Pengetahuan Menyikat Gigi antara Penyuluhan dengan Media Leaflet dan Media Flip Chart pada Anak Usia 12 Tahun - Sriani, Yustina; Azzahra, Hanifa Fatimah; Herawati, Nova; AlJufri, Aljufri; Alhamda, Syukra (Poltekkes Kemenkes Padang, 2023)
Dental health education is one way to increase knowledge about brushing teeth from school age. To increase knowledge of brushing teeth, you can use media such as leaflets and flip charts. The aim of this research was to determine differences in knowledge of toothbrushing education using leaflets and flip charts in 12 year old children at SDIT PERMATA, Padang City. This type of quasi-experimental research with a pre-test and post-test design. The population of all children aged 12 years was 32 people with the total sample population divided into 2 groups, namely 16 leaflet groups and 16 flip chart groups. The data collection instrument was a questionnaire. Data were analyzed using paired and independent t-tests. The results of the research show that respondents' knowledge after counseling using leaflet media increased by 100%, good criteria and flip charts increased by 68.8%, with good criteria, with the results of the paired t-test on leaflet media having a p value of 0.000 (p<0.05) while on flip chart media p value 0.000 (p<0.05). The results of the independent t-test obtained a p value of 0.002 (p<0.05), meaning that there was a difference in knowledge of brushing teeth after counseling with leaflet and flip chart media, where leaflet media was better in increasing knowledge of toothbrushing. It is recommended that students apply good and correct tooth brushing techniques, then brush their teeth at least twice a day, namely after breakfast and at night before bed.